2024
DOI: 10.5498/wjp.v14.i1.148
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between physical activity and specific working memory indicators of depressive symptoms in university students

Qun Zhao,
Xing Wang,
Shu-Fan Li
et al.

Abstract: BACKGROUND The detection rate of depression among university students has been increasing in recent years, becoming one of the main psychological diseases that endangers their physical and mental health. According to statistics, self-harm and suicide, for which there is no effective intervention, are the second leading causes of death. AIM To explore the relationship between different elements and levels of physical activity and college students’ depression-symptom-specific workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…This previous evidence contributes to solidifying the positive association between PA and EFs in university students. Complementary to the above, a recent study concluded that increasing PA could improve working memory performance in college students [79]. Building on previously reported findings, it is suggested that during university, exercise may be linked to better cognitive flexibility [80].…”
Section: Discussionmentioning
confidence: 69%
“…This previous evidence contributes to solidifying the positive association between PA and EFs in university students. Complementary to the above, a recent study concluded that increasing PA could improve working memory performance in college students [79]. Building on previously reported findings, it is suggested that during university, exercise may be linked to better cognitive flexibility [80].…”
Section: Discussionmentioning
confidence: 69%